Implementing participation‐focused services: A study to develop the Method for using Audit and Feedback in Participation Implementation (MAPi). (8th January 2020) - Kolehmainen, Niina; Marshall, Joanne; Hislop, Jenni; Fayed, Nora; Kay, Diane; Ternent, Laura; Pennington, Lindsay
Abstract: Background: It is widely agreed that children's services should use participation‐focused practice, but that implementation is challenging. This paper describes a method for using audit and feedback, an evidence‐based knowledge translation strategy, to support implementation of participation‐focused practice in front‐line services, to identify barriers to implementation, and to enable international benchmarking of implementation and barriers. Method: Best‐practice guidelines for using audit and feedback were followed. For audit, participation‐focused practice was specified as clinicians' three observable behaviours: (a) targets participation outcomes; (b) involves child/parent in setting participation outcomes; and (c) measures progress towards participation outcomes. For barrier identification, the Theoretical Domains Framework Questionnaire (TDFQ) of known implementation barriers was used. A cycle of audit and barrier identification was piloted in three services ( n = 25 clinicians) in a large U.K. healthcare trust. From each clinician, up to five randomly sampled case note sets were audited (total n = 122), and the clinicians were invited to complete the TDFQ. For feedback, data on the behaviours and barriers were shared visually and verbally with managers and clinicians to inform action planning. Results: A Method for using Audit and feedback for Participation implementation (MAPi) was developed. The MAPi audit template captured clinicians' practices: Clinicians targeted participation in 37/122 (30.3%) of the sampled cases; involved child/parent in 16/122 (13.1%); and measured progress in 24/122 (19.7%). Barriers identified from the TDFQ and fed back to managers and clinicians included clinicians' skills in participation‐focused behaviours (median = 3.00–5.00, interquartile range [IQR] = 2.25‐6.00), social processes (median = 4.00, IQR = 3.00–5.00), and behavioural regulation (median = 4.00–5.00, IQR = 3.00–6.00). Conclusions: MAPi provides a practical, off‐the‐shelf method for front‐line services to investigate and support their implementation of participation‐focused practice. Furthermore, as a shared, consistent template, MAPi provides a method for generating cumulative and comparable, across‐services evidence about levels and trends of implementation and about enduring barriers to implementation, to inform future implementation strategies.